Seismotectonics of the Panama Triple Junction region revealed by recent seismicity - Linkimer Abarca, Lepolt (2026)
The interaction among the Cocos, Nazca, and Panama plates at the Panama Triple Junction (PTJ) generates diverse seismic sources that remain poorly characterized. Using data from the National Seismological Network of Costa Rica and the Chirinet network of Panama, we analyzed four recent earthquake sequences (Mw 5.6–6.2, 2019–2021) near the Burica Peninsula and relocated 32 significant events (Mw 5.6–6.7) that occurred between 2000 and 2025. The results reveal: (1) right-lateral strike-slip faulting along the Panama and Balboa fracture zones; (2) right-lateral faulting on their inland projections, including the 2019 Mw 6.0 Canoas Fault earthquake; (3) reverse faulting during the 2008 (Mw 5.6) and 2020 (Mw 5.6) North Burica sequences, associated with the Media Fault Zone of the upper Panama Plate; (4) left-lateral strike-slip faulting within the subducting Cocos Plate, where at least five Mw 5.8–6.5 events occurred between 2002 and 2019; and (5) a seismogenic Cocos–Panama interplate zone extending southeast of the Burica Peninsula. We further reinterpret the 1934 Ms. 7.6 Armuelles tsunamigenic earthquake as a large megathrust rupture on this interplate boundary. Together, these findings refine the geometry of the seismic sources near the PTJ improving our understanding of the tectonic processes shaping the region.